Customer Satisfaction with Community Pharmacy Services and Its Determinant in Indonesia: A Cross-sectional Survey - Yuliani, Rizka Prita; Muin, Fathul; Farrukh, Muhammad Junaid; Pribadi, Prasojo (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Assessing customer satisfaction and its determinants are important for evaluating the quality of pharmaceutical services and identifying areas for improvement.Objectives: This study aims to evaluate the level of customer satisfaction and identify key factors associated with it.Methods: A cross-sectional study was conducted in 10 pharmacies located in Yogyakarta, Surakarta, and Magelang cities, involving a total of 1,200 customers. Data was collected using a validated patient satisfaction questionnaire from previous study and analyzed using SPSS 20 software. It was interviewed questionnaire that consists of three domains: sociodemographic characteristics, patient satisfaction, and opinions on service improvement in the community pharmacies. The inclusion criteria were customer who received services at community pharmacies between July and August 2021. Customers who were sick and unable to participate in an interview were eliminated from the study.  Results: The average overall satisfaction score obtained was 3.46 (SD ±0.34). The average customer satisfaction scores were as follows: facilities (3.92 ± 0.45), waiting time (3.76 ± 0.59), medicine stocks (3.54 ± 0.61), staff availability (3.25 ± 0.53), and counseling hours (3.18 ± 0.54).Conclusion: Overall, customers are quite satisfied with the community pharmacy services. There is a relationship between age, residence, education level, type of medicine, payment method, and experience in using pharmacy with customer satisfaction level. Community pharmacists should prioritize improving service quality by focusing on enhancing customer counseling and pharmacists’ skills in communication.